Statement of Foliar Fertilization Impact on Yield, Composition, and Oxidative Biomarkers in Rice - Pinciroli, María (2019)
In rice crops, fertilization is a naturalized practice, although inefficient, that could be improved by applying foliar fertilization. Phytoprostanes (PhytoPs) and phytofurans (PhytoFs) are products of α-linolenic acid peroxidation, useful as biomarkers of oxidative degradation in higher plants. The objective was to determine the effect of the foliar fertilization on the concentration of PhytoPs and PhytoFs and its relationships with modifications of yield and quality of rice productions. It was described that the concentration of biomarkers of stress decreased with the application of foliar fertilization, being the response significantly different depending the genotypes and compound monitored. Moreover, fertilization did not modify significantly the parameters of yield (961.2 g m−2), 1000 whole-grain (21.2 g), and protein content (10.7% dry matter). Therefore, this is the first work that describes the effect of fertilization on PhytoPs and PhytoFs in rice genotypes and reinforces the capacity of these compounds as biomarkers to monitor specific abiotic stress, in this case, represented by nutritional stress.